Disk supported carbon membrane derived from based polymer polyimide for carbon dioxide related separation - Ismail, Nor Hafiza (2017)
Carbon membrane is known as a promising alternative for gas separation and has commonly been used for carbon dioxide (CO2) separation. However, the challenge for the carbon membrane to be practically used is the difficulty of getting a good mechanical strength and defect-free membrane. In this study, a 4,4’- benzophenone tetracarboxylic dianhydride and 80% methyl phenylene- diamine plus 20% methylene diamine known as P84 were selected as the polymeric precursors and porous alumina disk as the supporting material. P84 has a superior gas separation performance, while the supporting material enhanced the mechanical strength of the carbon membrane. The preparation of the carbon membranes involved two main steps, which were polymeric membrane preparation and carbonization process. The polymeric membrane was prepared by a spray coating technique to obtain thin and defect-free carbon membrane layer. The carbon membrane was prepared at 600 to 900 °C under nitrogen (N2) gas flow of 200 mL/min and heating rate of 3 °C/min. The alumina powder was utilized as an intermediate layer to decrease the penetration of the polymer solution within the porous alumina supporting material. The optimum composition of polymer precursor was studied to determine the best polymer formulation for disk-supported carbon membrane. During the carbonization process, the effect of carbonization temperature was investigated. The properties of the fabricated carbon membrane were characterized and analyzed in terms of their morphological structure and thermal properties. Pure gas permeation tests using pure gases (CO2, N2 and methane (CH4)) were conducted at a room temperature and 4 bars. The CO2/N2 and CO2/CH4 selectivity of 24.54 and 65.43, respectively, were obtained for carbon membrane prepared with 12 wt% of the P84 by utilizing alumina powder as intermediate layer and after it was carbonized at 800 °C. As a conclusion, the disk supported carbon membrane was successfully fabricated and able to facilitate the development of gas purification technology.